2015
DOI: 10.4309/jgi.2015.31.7
|View full text |Cite
|
Sign up to set email alerts
|

Raisons de jouer, _motions et perceptions relatives au hasard et à l'habilet_ de joueurs pratiquant le poker Texas Hold'em en ligne

Abstract: RésuméBien que la pratique du poker en ligne se trouve associée à des taux élevés de problèmes de jeu, on en sait encore peu sur ce qui distingue, dans ce cas particulier, les joueurs présentant des niveaux de problème de jeu différents. Trois groupes de joueurs (à faible risque (n = 7), à risque (n = 7) et problématiques (n = 3)) qui pratiquent le poker Texas Hold'em en ligne ont été comparés sur le plan de leurs raisons de jouer, des émotions vécues au jeu et de leurs perceptions relatives au hasard et à l'h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
(46 reference statements)
0
4
0
2
Order By: Relevance
“…The importance of the perception of control over the game's outcome, or not questioning one's skill level with respect to gambling problem severity were also emphasized in the results of focus groups conducted with online poker players (no problem, at-risk, and problem; Brochu et al, 2015). The beliefs verbalized in the at-risk and problem groups, such as the importance of practice, acquiring knowledge, and learning from one's losses showed that these gamblers consider skill to be more important than non-problem gamblers, as the latter did not display this type of belief.…”
Section: Erroneous Beliefs Relating To Illusions Of Controlmentioning
confidence: 99%
“…The importance of the perception of control over the game's outcome, or not questioning one's skill level with respect to gambling problem severity were also emphasized in the results of focus groups conducted with online poker players (no problem, at-risk, and problem; Brochu et al, 2015). The beliefs verbalized in the at-risk and problem groups, such as the importance of practice, acquiring knowledge, and learning from one's losses showed that these gamblers consider skill to be more important than non-problem gamblers, as the latter did not display this type of belief.…”
Section: Erroneous Beliefs Relating To Illusions Of Controlmentioning
confidence: 99%
“…ex., GBQ-I; Steenbergh et al, 2002;IBS;Jefferson & Nicki, 2003;PPLS;Wohl et al, 2005;GABS;Breen & Zuckerman, 1999, GRCS;Raylu & Oei, 2004) par le fait qu'il a été spécifiquement conc¸u pour être administré à des parieurs de loteries sportives. Le développement de mesures spécifiques aux jeux d'habileté répond aux critiques exprimées à l'égard des questionnaires existants, qui ne seraient pas adaptés aux caractéristiques spécifiques de ces jeux (Barrault & Varescon, 2012;Bjerg, 2010;Brochu et al, 2015;Devynck et al, 2012).…”
Section: Forces Et Limitesunclassified
“…This phenomenon affects emotional and cognitive behaviors and is associated with dissociative experiences. These episodes can be caused by internal (frustration, tiredness) or external events (statistically improbable sudden loss, long series of small losses), which collectively result in a feeling of frustration [ 7 , 8 , 9 , 10 , 11 ]. There are many consequences of these tilt episodes for players.…”
Section: Introductionmentioning
confidence: 99%